Pengaruh Penggunaan Uang Tunai dan Transaksi Non-Tunai Terhadap Tingkat Konsumtif Mahasiswa Fakultas Hukum Universitas Buana Perjuangan Karawang Angkatan 2022 - Najwa Hanuni Hapi; Ujang Suherman; Thomas Nadeak (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine the effects of cash usage and non-cash transactions on students’ consumptive behavior, both partially and simultaneously. This study employed a quantitative approach involving 102 students from the Faculty of Law at Universitas Buana Perjuangan Karawang, Class of 2022. The results of multiple linear regression analysis indicate that cash usage does not have a statistically significant partial effect on students’ consumptive behavior, whereas non-cash transactions have a positive and statistically significant effect. Simultaneously, cash usage and non-cash transactions significantly influence students’ consumptive behavior. The coefficient of determination (R²) of 0.859 indicates that 85.9% of the variation in consumptive behavior is explained by the two independent variables, with non-cash transactions emerging as the dominant factor driving increased consumptive behavior. This study strengthens empirical evidence on the cashless effect in students’ financial behavior and provides strategic implications for enhancing financial literacy and personal financial management amid the increasing adoption of digital payment systems.